Gene Annotation of Cancer Vaccine for Homo sapiens - Nimilita Chakraborty (International Journal of Molecular Biotechnological Research, 2024)
Objectives: Gene annotation helps us to deduce the structural and functional aspects of a gene that encodes for a functional protein in our body. Thus, by determining the coding sequence and gene location we can derive meaningful insights as to what these genes do in our body. In this study, an unknown gene, cancer vaccine for Homo sapiens has been studied and annotated. Methods: This study was based on a computational approach using various web interface tools to annotate an unknown gene taken from the NCBI Database. The chosen gene was structurally annotated using a GC% content calculator, visually represented using Microsoft Excel, Augustus for gene prediction, and RNAfold to determine the mRNA structure of the same gene. Functional annotation was done using BlastP, gene ontology was confirmed using the UniProt database, a phylogenetic tree was analyzed using HOGENOM database and TMHMM to visualize the transmembrane domain of the protein encoded by the gene, expression of the gene by Bgee, antibody analysis, subcellular localization, and functional analysis was accomplished using Human Protein Atlas, wolF PSORT and InterProScan respectively. Results: After completing the gene annotation, the cancer vaccine for Homo sapiens query was found to be 99.9% similar to four-jointed box protein 1 precursor [Homo sapiens] which exhibits low cancer tissue specificity and is mostly related to renal and urothelial cancer. Conclusion: The Cancer vaccine for Homo sapiens entry present in the NCBI Database, which had no annotation previously, was annotated structurally and functionally in this study. Now we can say this entry belongs to the gene coding for a four-box jointed protein-1 precursor protein which is useful for cancer diagnosis in the early stages and is related to poor prognosis of the disease. Often specific peptides are designed for FJX-1 protein which are beneficial in the treatment of cancers showing elevated expression of FJX1 proteins and are often used in the form of vaccines.
Keywords: Cancer; Gene prediction; local sequence alignment; mRNA structure; protein; transmembrane domain; vaccination